YOUTUBE TV : KONVERGENSI MEDIA PENYIARAN DIGITAL - prabowo, fadeyanto (Jurnal Ilmu Komunikasi AKRAB, 2025)
The advancement of the internet has driven cross – platform intregration, griving rise to the phenomenon of Social TV, with YouTube Channels serving as a prominent example of media convergence in Indonesia. This study aims to explore how YouTube Channels reflect the intersection between digital broadcasting and social media, as well as their influence on the audience’s shift from traditional to digital media. A text-based qualitative method was employed to examine this phenomenon in depth. The findings reveal that while the platform allows users creative freedom, the absence of specific regulations opens the door to irresponsible content production and negative user interactions. Therefore, there is a pressing need for clear and effective regulations to ensure that digital content aligns with existing social norms and legal frameworks.